Adult-Onset Niemann–Pick Disease Type C: Rapid Treatment Initiation Advised but Early Diagnosis Remains Difficult - Piroth, Tobias; Boelmans, Kai; Amtage, Florian; Rijntjes, Michel; Wierciochin, Anna; Musacchio, Thomas; Weiller, Cornelius; Volkmann, Jens; Klebe, Stephan (Frontiers in Neurology, 2017)
Niemann-Pick type C disease (NP-C) presents with heterogeneous neurological and psychiatric symptoms. Adult onset is rare and possibly underdiagnosed due to frequent lack of specific and obvious key symptoms. For both early and adolescent/ adult onset, the available data from studies and case reports describe a positive effect of Miglustat (symptom relief or stabilization). However, due to the low frequency of NP-C, experience with this therapy is still limited. We describe two adult-onset cases of NP-C. In both cases, vertical supranuclear gaze palsy was not recognized at symptom onset. Correct diagnosis was delayed from onset of symptoms by more than 10 years. The video demonstrates the broad spectrum of symptoms in later stages of the disease. Compared with published data, the treatment outcome observed in our cases after delayed initiation of Miglustat therapy was disappointing, with continuing disease progression in both cases. Thus, early treatment initiation could be necessary to achieve a good symptomatic effect. Hence, early biochemical testing for NP-C should be considered in patients suffering from atypical neurological/neuropsychological and psychiatric symptoms, even in cases of uncertainty.